Effect of aqueous extract of olea europea l. plant in biochemical , oxidation parametrs in male rats treated with cyclophosphamide - ابراهيم احسان ريسان (University of Thi-Qar Journal of Science, 2014)
This study was conducted to determine the role of extract of Olea europea L. to reduce the negative effects of cyclophosphamide in some biochemical, oxidation aspects. male rats divided into three groups first group injectedwith distilled water was given ip. The second group injected ip with cyclophosphamide at dose (50 mg / kg) for 14 days the third group was given also drug with the dose (50 mg / kg) for 14 days then treated animals were given extract at dose (300 mg / kg) for 14 days. Samples of blood were collected and isolated serum , the parameters in study were included lipid profile (total cholesterol ,high density lipoprotien ,low density lipoprotien and triglycerides) ,enzymes( GPT, GOT, ALP)and glucose also included anti-oxidant(Glutathione) and lipid peroxidation (Malondialdehayde). Results showed a significant increase in enzymes (GPT, GOT, ALP), LDL, total cholesterol, triglyceride and malondialdehyde in while appear significant decrease in glutathione, glucose and HDL in drug injected group compared with the control group. While the extract treatment group caused decreased significantly in enzymes (GPT, GOT, ALP), LDL, TG, Cholesterol and Malondialdehayde, while show results increase in glutathione, glucose and HDL compared with drug injected group. concluded the ability of aqueous extract of Olea europea L. to reduce some of the negative effects of drug cyclophosphamide in white rats.